2021
DOI: 10.33667/2078-5631-2021-3-48-56
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders in doctors in the context of the COVID-19 pandemic

Abstract: Study. The relationship of sleep disorders with anxiety in practicing neurologists in the context of a pandemic. Goals. To assess the quality of sleep, the level of anxiety and their mutual influence in neurologists.Design. 330 neurologists were interviewed using the GoogleForms service, using the questionnaire "The psychological impact of the coronavirus pandemic on the population is measured using the Psycho-Covid‑19 questionnaire" in partnership with an international group of researchers led by VitoTummino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Based on these studies, coping strategies were suggested. For instance, social support can improve the mental health of medical staff, who treat patients with COVID-19, and reduce the risk of sleep disorders, associated economic losses, unintentional medical errors and reduced working efficiency [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these studies, coping strategies were suggested. For instance, social support can improve the mental health of medical staff, who treat patients with COVID-19, and reduce the risk of sleep disorders, associated economic losses, unintentional medical errors and reduced working efficiency [27][28][29].…”
Section: Introductionmentioning
confidence: 99%